Effect of diet containing alfalfa (Medicago sativa) powder and leaf extract on hemolymph factors of western whiteleg shrimp (Litopenaeus vannamei) under low salinity stress - Kobra Babanejad Abkenar; Arash Akbarzadeh; Ahmad Noori; Mohammad Niroomand (تغذیه آبزیان)
ntroduction: The western whiteleg shrimp, Litopenaeus vannamei, is a euryhaline species, but fluctuated salinity can lead to stress. Hemolymph indices, such as total and differential hemocyte counts, are key indicators of immune status in shrimp. Using medicinal plants to feed farmed aquatic animals is a promising approach to enhance production performance and resilience to environmental stress. Alfalfa, Medicago sativa leaves are used in animal and human diets due to high protein content and nutritional value. This study evaluates the impact of alfalfa leaf powder (ALP) and extract (ALE) on the hemolymph indices of L. vannamei in low salinity stress conditions. Materials and methods: Shrimp were fed in seven treatments with three replications, including control (without ALP and ALE), ALP (60, 120, and 180 g/kg), and ALE (6, 12, and 18 g/kg) for nine weeks. Then, the shrimp were subjected to salinity stress at five ppt for 48 hours. Survival rates were recorded at the end of the feeding and stress period, and total and differential hemocyte counts were measured. Results: In non-stress conditions, the number of hemocytes in the control group was significantly lower compared to the other treatments. In the 5 ppt salinity, ALP180 and ALE18 showed significantly higher total hemocyte counts than the control group (p<0.05). In both salinity conditions, the control treatment had a significantly higher number of hyaline cells compared to other treatments. In the control and ALP180 treatments, the numbers of hyaline cells were higher in the normal salinity than in the five ppt (p<0.05). Moreover, in the normal salinity, the number of large granular cells was significantly lower in the control group than in the other treatments. In addition, in the control group, large granular cells in the five ppt were significantly higher than the control group in normal salinity (p<0.05).  The survival rate was significantly higher in treatments fed with ALP and ALE in normal salinity compared to the control. In 5 ppt salinity, survival rates were also significantly higher in the ALP180 and ALE18 compared to the control (p<0.05). Discussion: Alfalfa leaves, rich in minerals like copper and iron and active compounds like flavonoids, contribute to increased hemocyte levels. Flavonoids interact with hemocyte cell receptors, promoting effective cell function. Hemocytes are crucial in crustaceans' defense against pathogens. A higher proportion of semi-granular cells in the western whiteleg shrimp indicate a stronger immune response. Additionally, xanthophyll and loliolide in alfalfa have germicidal properties and help to improve the survival rate. Conclusion: This study demonstrates that alfalfa leaf powder and extract positively impact shrimp's survival and immune system function under low salinity stress.